The Kidneys and the Liver as the Organs Regulating the Fibrinolytic System of the Circulating Blood - Januszko, T; Furman, M; Buluk, K (Thrombosis and Haemostasis, 1966)
In experiments on rabbits it was shown by means of interruption and reestablishment of hepatic and renal circulation that these organs play an essential role in the regulation of the fibrinolytic system of the circulating blood. The kidneys are the source of the plasminogen activator secreted in the blood whereas the liver is responsible for the inactivation of the fibrinolytic system.